Cover Image, Volume 138, Issue 24. Issue 24 (12th March 2021) - Ali, Nisar; Ali, Farman; Saeed, Shaukat; Said, Amir; Sheikh, Zeshan Ali; Salman, Syed Muhammad; Bilal, Muhammad
Abstract : This cover designed by Muhammad Bilal and colleagues represents the brittle fractured surface of unmodified silica microparticles, which are spherical with sharp boundaries and smooth surfaces, suggesting no chemical interaction between two boundaries. The silica particles seem to be out of their grooves, as there was no chemical interaction between the two phases i.e., organic, and inorganic. Wide gaps between polyimide matrix and silica microparticles expose the weak interfacial interaction between organic‐inorganic components. This phase separation and immiscibility in the case of unmodified silica nanoparticles result in the stress amount defect instead of effective strengthening constituents. 10.1002/app.50646